Den grundtvigske arv: Christian Hostrup som prædikant med særligt blik på de grundtvigske elementer - Thodberg, Christian (Grundtvig-Studier, 1977)
The Grundtvig Heritage: Christian Hostrup as Preacher, with a Special Consideration of the Grundtvig Elements in his Sermons by Christian Thodberg Jens Christian Hostrup (1818-92) was one of Grundtvig’s most important heirs. Hostrup drew nearer to Christianity and to Grundtvig as a result, amongst other things, of the attack which Søren Kierkegaard launched on the official Church in the 1850’s. It was for this reason that in particular the sermon aimed at saving souls and formulated in simple language became a characteristic of Hostrup as a preacher. He did not take holy orders until he was a man of mature years with a praiseworthy career as a playwright behind him. Hostrup takes over Grundtvig’s words and concepts but attributes a different meaning to them. The renunciation of the devil and the creed, for example, were to Grundtvig a message with a personal address by virtue of the interrogative form used in the baptism ritual, but for Hostrup the renunciation and the creed in the form in general use become a minimum demand on the tempted believer. Above all he emphasizes a personal awareness of the relationship with God. Whereas Grundtvig returned to baptism and dramatically relived it, baptism for Hostrup is to be supplemented by a growing awareness in the mature Christian. Most instructive is the relationship between Grundtvig and Hostrup as analysed in their use of the word heart. For Grundtvig heart is often used in conjunction with mouth, tongue, word and ear. This pattern stresses man’s extrovert nature towards God and his fellow man. Thus for Grundtvig the heart is the subject of a series of distinctive verbs of experience, emphasizing the image of God and its dynamic character in the heart. It is different with Hostrup; for him the heart becomes exclusively the seat of religious awareness. Attention is centred to a great degree on the heart’s feelings that the truth and the power in God’s Word can only be received through the heart’s sensitivity, through its desire and its aspiration. The heart is thus made independent, but becomes at the same times an expression of man’s loneliness: man can go only so far as the heart will allow. Thus for Hostrup the heart is almost static, in contrast to the dynamic character it had for Grundtvig as a mirror of God’s love - as an ear and a sounding-broard for God’s word. With its background in a structuralist examination of Grundtvig’s words and concepts in the present book the paper proves that a corresponding examination of the words and concepts of one of Grundtvig’s heirs gives a precise specifi308 cation of the characteristic differences. In Grundtvig and Hostrup we find the same words and concepts, but the patterns into which they fit are different. A structuralist analysis is therefore useful for an investigation into what happens when a tradition is handed on and taken over.